Development stages of a semi-autonomous underwater vehicle experiment platform. (31st May 2022) - Serhat, YILMAZ
The design of underwater unmanned vehicles is an interdisciplinary study that includes several fields, such as computational fluid dynamics, modeling and control of systems, robotics, image processing, and electronic card design. The operational cost of such vehicles is high because it is dependent on variable fluid properties like salinity and high pressure while its' mobility must be resistant to environmental conditions such as undersea. The study describes an operating platform, called Lucky Fin, on which the students can develop various control algorithms and can test and extract hydrodynamic parameters of the underwater vehicle. The platform consists of an underwater vehicle and two testing tanks. The control card, the user control program interface, and a manipulator's arm are designed to be used for a series of control applications such as depth, heading, target tracking, and capturing. The results of several tests are illustrated in this article.